Hibernate recipes a problem-solution approach - Ottinger, Joseph; Guruzu, Srinivas; Mak, Gary (Apress, 2015)
Hibernate Recipes , Second Edition contains a collection of code recipes and templates for learning and building Hibernate solutions for you and your clients, including how to work with the Spring Framework and the JPA. This book is your pragmatic day-to-day reference and guide for doing all things involving Hibernate. There are many books focused on learning Hibernate, but this book takes you further and shows how you can apply it practically in your daily work. Hibernate Recipes, Second Edition is a must have book for your library. Hibernate 4.x continues to be the most popular out-of-the-box, open source framework solution for Java persistence and data/database accessibility techniques and patterns and it works well with the most popular open source enterprise Java framework of all, the Spring Framework. Hibernate is used for e-commerce-based web applications as well as heavy-duty transactional systems for the enterprise.
Includes index. - Place of publication taken from publisher's Web site. - Online resource; title from cover page (Safari, viewed March 31, 2015)
Keywords: Hibernate (Electronic resource); Java (Computer program language); Java (Langage de programmation)